ПИТАННЯ ПІДВИЩЕННЯ ТОЧНОСТІ ОЦІНОК ДІАГНОСТИЧНИХ ОЗНАК ПРИ СПЕКТРАЛЬНІЙ ОБРОБЦІ ВІБРАЦІЙНИХ СИГНАЛІВ - Гижко, Ю.І.; Мислович, М.В.; Сисак, Р.М. (Інститут електродинаміки НАН України, Київ, 2012)
The software was developed for spectral analysis of diagnostic signals with improved characteristics of accuracy and reliability due to application of spectral windows. With usage of computer simulation, the influence of shape and parameters of spectral windows on the accuracy of estimations of spectral diagnostic parameters was investigated. For this, the simulation of vibration signals realization with defined spectral parameters was performed, after which the statistical spectral analysis of these realizations was performed with smoothing with usage of different types of spectral windows. The influence of parameters of spectral windows on the accuracy characteristics of the spectral analysis of investigated signals was noticed. References 5.